The Existence of The Implementation of The Academic Ability Test in Increasing The Learning Motivation of Package C Students at PKBM Bina Bangsa Purwakarta - Deni Hidayah; Ade Siti Rosmuliawati; Suharyanto H Soro; Dinny Mardiana (Global Education Journal, 2025)
This research is based on the phenomenon of low student attendance before the implementation of TKA, which then increases after TKA is implemented. This study aims to describe the existence of the implementation of the Academic Ability Test (TKA) and analyze its influence on the learning motivation of Package C students at PKBM Bina Bangsa Purwakarta. This research method uses a qualitative descriptive approach with data collection techniques in the form of observation, semi-structured interviews, and documentation. The research population consisted of all Package C students at PKBM Bina Bangsa, with a purposive sample that focused on students with low attendance rates before TKA. The results of the study show that the implementation of TKA at PKBM Bina Bangsa Purwakarta is carried out in a planned manner, and integrated with the learning process. TKA not only functions as an academic evaluation instrument, but is also used as a means of reflection on learning by tutors and a tool to strengthen learning motivation for students. The contribution of foreign workers to learning motivation can be seen from changes in students' learning behavior, especially increased attendance, discipline, and active involvement in learning activities. Based on these results, it can be concluded that the Academic Ability Test has a real and significant existence in increasing students' motivation to learn, especially through increased attendance and active involvement in the classroom. This study provides recommendations for PKBM to maintain the implementation of TKA regularly, provide constructive feedback, and integrate TKA with other motivational strategies to maximize student learning outcomes.